The tornado twins - Lyga, Barry (Lyga, Barry. Flash, 2018)
Barry Allen faces his greatest challenge yet--running into the future sixty-fourth century. In order to complete his mission, he must face the evil Abra Kadabra and uncover the well guarded secrets of Hocus Pocus. And back on Earth One, Kid Flash is on his own mission--to stop Earthworm before he strikes again.